Respect your elders: effects of ageing on intracranial pressure monitor use in traumatic brain injury. Issue 1 (17th June 2019) - Schupper, Alexander J; Berndtson, Allison E; Smith, Alan; Godat, Laura; Costantini, Todd W
Abstract : Background: The Brain Trauma Foundation recommends intracranial pressure (ICP) monitor placement for patients with severe traumatic brain injury (TBI). Adherence with these guidelines in elderly patients is unknown. We hypothesized that disparities in ICP monitor placement would exist based on patient age. Methods: Using the National Trauma Data Bank (2010–2014), we identified patients admitted for blunt TBI with admission Glasgow Coma Scale (GCS) scores of 3–8. Patients were excluded if they had a non-Head Abbreviated Injury Scale (AIS) score ≥3, hospital length of stay <24 hours or were discharged from the emergency department. Demographic data, ICP monitor placement, GCS, AIS-Head, Injury Severity Score, and outcome measures were collected. Propensity score matching between ICP monitor and non-ICP monitor patients was used for logistic regression and Cox multivariate regression analyses. Results: Of the 30 710 patients with blunt TBI with GCS scores of 3–8 included in our study, 4093 were treated with an ICP monitor. ICP monitor placement rates significantly decreased with increasing age. Multivariable analysis demonstrated that patients treated with an ICP monitor were more likely to be younger, male, have private/commercial insurance, and receive care at an institution with three or more neurosurgeons. Conclusion: Patients ≥65 years of age with severe blunt TBI are less likely to be treated with an ICP monitor than younger patients. Age disparities in adherence to Brain Trauma Foundation guidelines may alter the outcomes for patients with severe TBI. Level of evidence: Level IV.